Provisions and accrued liabilities in the light of the polish balance law and international accounting standards - Kister, A. (Видавництво Львівської політехніки, 2012)
Розмір резервів підприємства є однією з основних категорій виміру фінансового стану та рентабельності. Їх формування повинно відповідати принципу достовірної й об'єктивної оцінки підприємства. Розглянуто сутність резервів, подано їх класифікацію. Докладно окреслено резерви і реструктуризацію та поточні розрахунки. Метою є також порівняння резервів у польському законодавстві та в Міжнародних стандартах фінансової звітності № 37. Provisions in accounting are one of basic categories of measurement of the financial situation and profitability. Creating them must be in accordance with the principle of accurate and reliable image of the enterprise. In the article the essence of provisions and their classification was described. In detail provisions were discussed to provisions for restructuring and accruals. The purpose of the article is to present provisions in perspective of the Polish balance law and IAS 37.